The Onset of Falls Reduces Subjective Well-Being. Findings of a Nationally Representative Longitudinal Study - Hajek, André; König, Hans-Helmut (Frontiers in Psychiatry, 2021)
Abstract Introduction: The prevalence of older individuals experiencing a fall is high. Moreover, falls can have deleterious effects on health status. Additionally, falls can affect the subjective well-being of individuals. However, there is a lack of studies examining the link between falls and subjective well-being. Therefore, the objective of this study was to investigate whether the onset of falling is associated with (intraindividual) decreases in subjective well-being in men and women. Materials and Methods: Longitudinal data (from wave 5 to wave 6) were taken from a population-based sample of individuals residing in private households in Germany (in our analytical sample: 3,906 observations (men), and 3,718 observations (women)). Positive and negative affect were quantified using the Positive and Negative Affect Schedule (PANAS). Life satisfaction was assessed using the Satisfaction with Life Scale (SWLS). Results: Adjusting for various potential confounders, fixed effects regressions showed that the onset of falls was associated with a decrease in positive affect (β=.08, p<.01), and an increase in negative affect (β=.07, p<.01) among men. While the onset of falls was not associated with changes in positive affect in women, it was associated with a decrease in negative affect in women (β=.06, p<.05). GenderSex differences were significant. The onset of falls was not associated with decreases in life satisfaction in men, nor in women. Discussion: The present study particularly highlights the link between the onset of falls and reduced affective well-being among men. Avoiding falls may contribute to maintaining affective well-being among middle-aged and older men.